As versões judaico-cristãs sobre o Debate de Barcelona em 1263: um estudo sobre identidades e fronteiras com base n’A vikuah de Nahmânides e n’O Relato Cristão - Santos, Regilene Amaral dos (2020)
The Barcelona Debate in 1263 was an event promoted by the Dominican Order in conjunction with the Catalan-Aragonese monarchy. At the time, a convert, friar Pablo Christiani, and a Catalan rabbi, Moses ben Maimon, discussed the motion that there were writi